Development and validation of molecular methodologies to assess PALB2 expression in sporadic breast cancer - Poumpouridou,N.; Acha-Sagredo,A.; Goutas, N.; Vlachodimitropoulos, D.; Chatziioannidou,I.; Lianidou,E.; Liloglou,T.; Kroupis, C. (Clin.Biochem., 2016)
OBJECTIVES: Recent reports have included PALB2 (Partner and localizer of BRCA2) in the growing list of hereditary cancer genes. PALB2 mutations confer a moderate breast cancer risk in heterozygotes and Fanconi anemia in biallelic mutation carriers. PALB2 protein co-localizes with BRCA2 and BRCA1 in nuclear structures and enables error-free homologous recombination repair of double-stranded DNA breaks. This important contribution could be severely diminished if affected by epigenetic mechanisms such as promoter CpG island methylation. The aim of our study was to develop molecular methodologies in order to assess accurately PALB2 expression in breast cancer tissues. DESIGN AND METHODS: DNA and RNA were extracted from 91 sporadic fresh-frozen breast tissues with known histopathological data. DNA was subjected to sodium bisulfite conversion reaction and the CpG island of the PALB2 promoter was analyzed by pyrosequencing. RNA was converted to cDNA and analyzed by a newly developed and validated RT-qPCR assay based on a hydrolysis probe (TaqMan) in the Light Cycler. RESULTS: PALB2 promoter was not methylated in any of the samples tested. 87 out of 91 (95.6%) primary tumors were positive for PALB2 expression, as checked at the mRNA level. When levels of PALB2 mRNA were compared to histopathological data (tumor size, grade, lymph node involvement, metastasis, hormone receptors and HER2 overexpression), no significant statistical correlation was found. CONCLUSIONS: DNA methylation is an unlike mechanism for PALB2 transcriptional regulation. PALB2 mRNA expression does not seem be a promising prognostic biomarker for sporadic breast cancer
DA - 20160206 IS - 1873-2933 (Electronic) IS - 0009-9120 (Linking) LA - eng PT - Journal Article PT - Research Support, Non-U.S. Gov't SB - IM